The Plays of Enda Walsh: An Interim Report - Murray, Christopher (Hungarian Journal of English and American Studies, 2020)
Ever since Disco Pigs hit the headlines at the Edinburgh Festival in 1996, Enda Walsh has achieved major success at home, on the Irish stage, and worldwide. This essay acknowledges that the body of his work to date, comprising nineteen plays plus collaborations in musicals and operas, still represents work in progress and that it is not feasible yet to provide anything like a definitive assessment or interpretation. It is argued, nevertheless, that the work may be situated within the Irish dramatic tradition and contemporary modes of performance. While Walsh seeks always to entertain through meta-theatre, his plays owe much not only to Beckett but also to youth theatre, especially to the style of Passion Machine, to story-telling techniques, and to clowning, farce, and rock music. Certain serious themes recur, such as alienation, private versus public space, and death, which place Walsh in a category beyond “just play.” As scriptwriter for David Bowie’s last show, Lazarus, staged in New York in December 2015, he may be moving towards a synthesizing of ideas, style, and theme, thus moving collaboration to a new level. (CM)